2021
DOI: 10.1002/gps.5565
|View full text |Cite
|
Sign up to set email alerts
|

‘Breaking the silence’: Sexual victimisation in an old age psychiatry patient population in Flanders

Abstract: for their input during the questionnaire development. Also, we want to thank our co-interviewers Rosie De Vidts and Lisa Thibau for their time and dedication to this project. Many thanks to the staff of the Old Age Psychiatry Departments of AZ Sint-Jan Bruges-Ostend AV, Psychiatric Hospital Karus and Psychiatric Hospital Alexianen Zorggroep Tienen for their support during the data collection process. Finally, we would like to thank Dr. Howard Ryland for his help with the language editing..

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…Recent research has shown that 60% of older SV victims never disclosed their experiences to their informal network, and 94% never sought professional help [ 50 ]. Similar to younger victims [ 51 ], older SV victims experience many barriers to disclose SV experiences or seek professional help [ 20 , 50 ]. We hypothesize that social support is only beneficial for long-term mental health outcomes following sexual victimisation when the confidants are aware of the victim’s SV history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that 60% of older SV victims never disclosed their experiences to their informal network, and 94% never sought professional help [ 50 ]. Similar to younger victims [ 51 ], older SV victims experience many barriers to disclose SV experiences or seek professional help [ 20 , 50 ]. We hypothesize that social support is only beneficial for long-term mental health outcomes following sexual victimisation when the confidants are aware of the victim’s SV history.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, identifying as non-heterosexual has been associated specifically with SV in older adults and has also been linked to mental health problems in older age [ 4 , 19 ]. Additionally, a recent study showed that sexual victimisation remains largely undetected by mental health care workers [ 20 ]. Although the World Psychiatric Association (WPA) petitioned a routine inquiry on SV in all psychiatric assessments [ 21 ], health care workers lack the appropriate communication skills to adequately address SV in later life.…”
Section: Introductionmentioning
confidence: 99%
“…We assume this could be explained by SV disclosure. Research in younger populations showed that SV victims experience many barriers to disclosure (Dartnall & Jewkes, 2013), which was recently confirmed in a sample of older adults with mental health problems (Nobels et al, 2021b). We hypothesize that social support is only beneficial when the confidants are aware of the victim's SV history.…”
Section: Lifetime Sexual Victimisation Is Linked With Depression Anxiety and Ptsd In Older Adultsmentioning
confidence: 70%
“…Additionally, a recent study showed that sexual victimisation remains largely undetected by mental health care workers (Nobels et al, 2021b). Although the World Psychiatric Association (WPA) petitioned a routine inquiry on SV in all psychiatric assessments (Steward & Chandra, 2017), health care workers lack the appropriate communication skills to adequately address SV in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown a clear link between socio-economic status and poverty with SV. SV can jeopardize a person’s economic wellbeing, potentially leading to homelessness [ 98 , 99 ], unemployment, interrupted education and health, mental health [ 8 , 64 , 98 , 100 , 101 ], and other daily stressors and struggles which impact one’s socio-economic status. In turn, not being able to meet one’s basic needs can increase a person’s vulnerability to sexual victimization [ 101 , 102 ].…”
Section: Introductionmentioning
confidence: 99%